Issues and Challenges of Minutes Writing: A University Assistant Registrar’s Perspective - Denkyi, Charles (Ghana Journal of Higher Education Management, 2024)
This paper discusses the importance of minutes writing, the conventional structure of minutes and some implications for an Assistant Registrar as a secretary. It concludes that writing minutes can be tedious but worth doing with the needed and appropriate skill